2016
DOI: 10.1002/cplu.201600087
|View full text |Cite
|
Sign up to set email alerts
|

A Ternary Zn−Al−Ir Hydrotalcite‐Like Compound Exhibiting High Efficiency and Recyclability as a Water Oxidation Catalyst

Abstract: Herein it is shown that hydrotalcite‐like compounds (HTlcs), doped with a suitably reactive metal, can efficiently act as water oxidation catalysts. As a case study, a ternary HTlc of formula [Zn0.667Al0.306Ir0.027(OH)2]Cl0.333⋅0.6 H2O, in which iridium is homogeneously distributed into the octahedral sites of brucite‐type sheets, was prepared and tested as a heterogeneous water oxidation catalyst, using NaIO4 as a sacrificial oxidant. This HTlc showed excellent performance in terms of turnover frequency (up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 51 publications
3
38
0
Order By: Relevance
“…[24] Finally,i tw as shown that complex 4 (2.5 mm solution)g enerates IrO x NPs when reactedw itha250 mm NaIO 4 solution. [56,68] This points to the conclusion that, whatever the real active speciesi s, it musth ave ad imension smallert han that of 11 NPs (mean diameter of 2nm) and larger or equal than that of 10,s oi th as to be molecular in nature. [6,41,[61][62][63][64][65][66][67] Although NPso f11 could not be properly tested owing to their transformation back to 10 under our experimental conditions, the results herein reportedc learly indicatet hat their activity is smaller than that of molecular[ Ir(OH) 6 ] 2À (10), consistent with previously reported results indicatinga ni mprovement of performance when the dimensionality of the active species is decreased.…”
Section: Fitting Methodology and Analysis Of Kineticdatamentioning
confidence: 99%
“…[24] Finally,i tw as shown that complex 4 (2.5 mm solution)g enerates IrO x NPs when reactedw itha250 mm NaIO 4 solution. [56,68] This points to the conclusion that, whatever the real active speciesi s, it musth ave ad imension smallert han that of 11 NPs (mean diameter of 2nm) and larger or equal than that of 10,s oi th as to be molecular in nature. [6,41,[61][62][63][64][65][66][67] Although NPso f11 could not be properly tested owing to their transformation back to 10 under our experimental conditions, the results herein reportedc learly indicatet hat their activity is smaller than that of molecular[ Ir(OH) 6 ] 2À (10), consistent with previously reported results indicatinga ni mprovement of performance when the dimensionality of the active species is decreased.…”
Section: Fitting Methodology and Analysis Of Kineticdatamentioning
confidence: 99%
“…At the same time, the catalyst recovered after the first catalytic run exhibits essentially the same catalytic activity than in the first run (Figure , bottom). The recyclability of Ir‐doped ZnAl LDH WOC was further explored conducting up to ten consecutive runs without noticing any drop of activity, always obtaining a production of O 2 very close to 100 % compared to that expected based on the amount of used NaIO 4 …”
Section: Doped Layered Hydroxides As Heterogeneous Ir Wocsmentioning
confidence: 99%
“…Down: comparison between the catalytic activity of Run 1 (black line), Run 2 (red line) and supernatant (blue line) ([Ir] = 50 µM, [IO 4 – ] = 0.03 m , pH 7.7 by phosphate buffer). Adapted from ref …”
Section: Doped Layered Hydroxides As Heterogeneous Ir Wocsmentioning
confidence: 99%
See 2 more Smart Citations